Investigation of hydraulic jump by using the Moving Particle Semi-Implicit method - Yacobus Yulianto (Institut Teknologi Bandung, 2023)
Investigation of hydraulic jump is necessary to provide the required data in hydraulic structures. Simulations are an alternative to experiments for providing data. The objective of this modeling is to examine the impact of the reservoir level on the height after the jump and the distance of the jump from the front of the exhaust hole. The simulation was performed by using the Moving Particle Semi-Implicit method. The reservoir level was set to 10 m, 18 m, and 32 m with 18174, 23934, and 33942 particles of simulation, respectively. The obtained results indicate that the height of the reservoir after the jump is between 2.68 m and 3.60 m for an initial reservoir level of 10 m. For an initial reservoir level of 18 m, the height of the jump is between 2.90 and 5.18 m. The final height after the jump ranges from 2.98 m to 8.28 meters for an initial reservoir level of 32 m. Consistent with the findings of other researchers, the simulation outcomes are extremely favorable. The higher the reservoir level, the higher the height after the jump, according to the obtained results of this study. In addition, the distance of the jump from the front of the exhaust hole increases as the reservoir fills. Regarding the expansion of this study, additional research must be conducted to investigate this phenomenon in greater depth, particularly with regard to particle velocity during the hydraulic jump process.